Sustainability reporting and sustainable development goals: bibliometric analysis - Diamantina Amélia Parckings Tauro Cumbana; José Biléu Ventura (Cogent Business & Management)
This study evaluates 270 articles on sustainability report (SR) and sustainable development goals (SDG) using a bibliometric method with Biblioshiny package. Using quantitative and qualitative analysis, the study identifies protuberant authors, publications and themes. Spain leads the publications followed by Indonesia, UK, Italy and Australia. There are three areas of focus: the SR, sustainable development and corporate sustainability; performance, corporate social responsibility and governance; and sustainability, GRI and accountability. Also, the research highpoints 37 possible areas for imminent research, helping academics in distinguishing critical gaps in the field of SR and SDG. The implications and limitations of the research are presented, and upcoming lines of investigation are suggested.